Unified Protocol for the Transdiagnostic Treatment of Emotional Disorders in Group Format in Spain: Results of a Noninferiority Randomized Controlled Trial at 15 Months after Treatment Onset - Peris-Baquero, O.; Osma, J. (Depression and Anxiety, 2023)
Evidence-based psychological treatments (EBPT) are an effective and efficient solution for the treatment of emotional disorders (EDs). However, their implementation and dissemination are not yet widespread. The Unified Protocol for Transdiagnostic Treatment of EDs (UP), applied in a group format, could be an effective option to be implemented in specialized public mental health services in Spain. The sample consisted of 533 users of public specialized mental health centers (77.3% women), with a mean age of 42.0 years (SD=12.62), who were randomized to the UP in group format condition (n=277) or treatment as usual (specific cognitive behavioral therapy for each disorder in individual format, n=256). Assessments were performed at preintervention (T1) and at 3, 6, 9 and 15 months after treatment onset (T2, T3, T4, and T5, respectively). The results showed a main effect of time in both conditions for all primary outcomes (p<0.05) and no statistically significant Time∗Condition interaction. Similarly, the noninferiority tests showed that UP results were statistically noninferior compared to TAU. Effect sizes for psychological variables were higher in the UP condition at T5, even though the differences were not statistically significant. Statistically significant differences (p<0.05) in the evolution of the diagnostic criteria and comorbidity were found, with the highest percentage of patients no longer meeting main and secondary diagnosis criteria in the UP condition at all assessment moments (except for secondary diagnosis at T3). The results showed statistically significant differences in treatment retention between conditions at T5, being the UP condition the one with less dropouts. Finally, participants in the group UP condition showed high satisfaction with the treatment. The UP is an EBPT that has been shown to be effective when applied in groups and may represent an efficient option for its implementation in public mental health services in Spain. This trial is registered with NCT03064477.